Aspirin and Some Other Nonsteroidal Anti-Inflammatory Drugs Inhibit Cystic Fibrosis Transmembrane Conductance Regulator Protein Gene Expression in T-84 Cells. Issue Volume 8:Issue4/ 5(1999) (1999) - Tondelier, Danielle; Brouillard, Franck; Lipecka, Joanna; Labarthe, Régis; Bali, Moëz; De Beauregard, Marie-Ayliette Costa; Torossi, Tanja; Cougnon, Marc; Edelman, Aleksander; Baudouin-Legros, Maryvonne
Abstract : Cystic fibrosis (CF) is caused by mutations in the CF gene, which encodes CF transmembrane conductance regulator protein (CFTR), a transmembrane protein that acts as a cAMP-regulated chloride channel. The disease is characterized by inflammation but the relationship between inflammation, abnormal transepithelial ion transport, and the clinical manifestations of CF are uncertain. The present study was undertaken to determine whether three nonsteroidal anti-inflammatory drugs (NSAIDs) (aspirin, ibuprofen, and indomethacin) modulate CFTR gene expression in T-84 cells. Treatment with NSAIDs reduced CFTR transcripts, and decreased cAMP-stimulated anion fluxes, an index of CFTR function. However, the two phenomena occurred at different concentrations of both drugs. The results indicate that NSAIDs can regulate both CFTR gene expression and the function of CFTR-related chloride transport, and suggest that NSAIDs act via multiple transduction pathways.